Association of SENPs single-nucleotide polymorphism and breast cancer in Chinese population. Issue 6 (February 2019) - Cai, Jiaqin; Wei, Xiaoxia; Zhang, Guifeng; Sui, Yuxia; Zhuang, Jie; Liu, Zhenhua; Sun, Hong
Abstract : Abstract: SUMO-specific Cysteine Proteases (SENPs) have involvement in the initiation and progression of human cancers. In the present study, we evaluated the association of SENPs polymorphism with susceptibility as well as clinicopathologic features and patients' response of breast cancer (BC) in a Chinese population. We genotyped SENP1 (rs61918808), SENP2 (rs6762208), SENP7 (rs61697963) by sequencing in a case–control study including 210 BC patients and 225 healthy volunteers. Odds ratios (ORs) and 95% confidence intervals (CIs) were used to assume the association strength. No significant association was found between polymorphism of the 3 SENPs and BC susceptibility. However, SENP1 rs61918808 (C>T) and SENP7 rs61697963 (A>C) was associated with HER-2 expression ( P  < .05). SENP2 rs6762208(C>A) was correlated with increasing risk of lymph node metastases ( P  < .05). Among the patients who received neoadjuvant chemotherapy, T allele and TT genotype of SENP1 rs61918808 were less likely to achieve pCR ( P  < .05). We first reported SENPs variants were not associated with BC risk in Chinese population, but presented specific effect on clinicopathological features of BC. Moreover, SENP1 rs61918808 may be a predictor for the clinical response in local advanced BC patients who received neoadjuvant chemotherapy.